Charge Transport Modulation of a Flexible Quantum Dot Solar Cell Using a Piezoelectric Effect. Issue 3 (22nd September 2017) - Cho, Yuljae; Giraud, Paul; Hou, Bo; Lee, Young‐Woo; Hong, John; Lee, Sanghyo; Pak, Sangyeon; Lee, Juwon; Jang, Jae Eun; Morris, Stephen M.; Sohn, Jung Inn; Cha, SeungNam; et al.
Abstract: Colloidal quantum dots are promising materials for flexible solar cells, as they have a large absorption coefficient at visible and infrared wavelengths, a band gap that can be tuned across the solar spectrum, and compatibility with solution processing. However, the performance of flexible solar cells can be degraded by the loss of charge carriers due to recombination pathways that exist at a junction interface as well as the strained interface of the semiconducting layers. The modulation of the charge carrier transport by the piezoelectric effect is an effective way of resolving and improving the inherent material and structural defects. By inserting a porous piezoelectric poly(vinylidenefluoride‐trifluoroethylene) layer so as to generate a converging electric field, it is possible to modulate the junction properties and consequently enhance the charge carrier behavior at the junction. This study shows that due to a reduction in the recombination and an improvement in the carrier extraction, a 38% increase in the current density along with a concomitant increase of 37% in the power conversion efficiency of flexible quantum dots solar cells can be achieved by modulating the junction properties using the piezoelectric effect. Abstract : The modulation of the charge carrier transport in flexible quantum dot solar cells is demonstrated by harnessing the piezoelectric potential. Modulation of the junction properties by the piezoelectric potential results in a 37% enhancement in the power conversion efficiency, which is attributed to an efficient dissociation and extraction of the photogenerated charge carriers and a reduction in the nonradiative recombination.